2004
DOI: 10.1113/expphysiol.2004.027839
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine administration to influence human exercise capacity, perceived effort or hormone responses during prolonged exercise in a warm environment

Abstract: The purpose of the experiment was to examine whether selective serotonin (5-HT) re-uptake transporter blockade by paroxetine has any effect on perceived effort (RPE) during exercise or the time to reach volitional fatigue and on the prolactin and cortisol responses during prolonged exercise performed in a warm environment. Eight healthy males performed two cycle rides to exhaustion in a warm (32

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 50 publications
7
41
3
Order By: Relevance
“…Results revealed that concentric exercises elicited a greater perceptual response and cortisol response than eccentric exercises. A study by Strachan et al (38) found similar results when they compared the effects of amino acid supplements on perceived exertion and hormone responses during prolonged exercise. While the supplements appeared to have no effect on either perceived exertion or cortisol, both reacted similarly (increased) during each exercise trial.…”
Section: Cortisol and Ratings Of Perceived Exertion (Rpe)supporting
confidence: 51%
See 2 more Smart Citations
“…Results revealed that concentric exercises elicited a greater perceptual response and cortisol response than eccentric exercises. A study by Strachan et al (38) found similar results when they compared the effects of amino acid supplements on perceived exertion and hormone responses during prolonged exercise. While the supplements appeared to have no effect on either perceived exertion or cortisol, both reacted similarly (increased) during each exercise trial.…”
Section: Cortisol and Ratings Of Perceived Exertion (Rpe)supporting
confidence: 51%
“…Utter et al found that lower RPE was associated with lower cortisol values during a 3 hour treadmill run (42). Strachen et al also found that perceived exertion and cortisol responses were positively correlated during exercise (38). These studies provide evidence that ratings of perceived exertion may be indicative of physiological stress and may be related to the same physiological cues of cortisol.…”
Section: Correlation Of Cortisol and Rpementioning
confidence: 56%
See 1 more Smart Citation
“…Glucocorticoids maintain blood glucose levels by stimulating the release of AAs from muscle and promoting gluconeogenesis is and mobilization of fat stores [31]- [33]. Corticosterone is also a peripheral marker of central 5-HT activity [34] [35]. In our experiments, changes in TGF-β1 and corticosterone levels were correlated with decreased locomotor activity, providing evidence that these molecules are markers of fatigue.…”
Section: Discussionsupporting
confidence: 54%
“…However, the results are contradictory and inconclusive. Although data have demonstrated no effect of different serotonin reuptake inhibitors (pizotifen, fluoxetine, citalopam) on exercise performance in humans (Meeusen et al, 2001;Pannier et al, 1995;Parise et al, 2001;Roelands et al, 2009;Strachan et al, 2004), findings from Struder et al (1998) and W. M. Wilson et al (1992) indicate that fatigue occurs sooner with pharmacological augmentation of the brain's serotonergic activity by serotonin re-uptake inhibitor (paroxetine) supplements. These different outcomes might be explained by divergent exercise protocols, pharmacological manipulations, drug receptor specificity and drug dosages.…”
Section: Serotoninmentioning
confidence: 97%